Role of Spiritual Intelligence in Public Policy in the African American Pentecostal Church - Smith, James B. (Journal of pentecostal theology, 2021)
Abstract Although many U.S. faith-based organizations have become partners with the government, the African American Pentecostal Church ( aapc ), which holds spirituality as a means of serving humanity as its theological framework, has remained a silent partner in public policy engagement. With the framework of spiritual intelligence, this qualitative case study addresses the perceptions of African American Pentecostal leaders regarding how the church’s theology may have an impact on the public policy engagement of its parishioners. Twelve African American Pentecostal Bishops were interviewed, and data were coded and analyzed to identify themes. Results revealed that participants use their spirituality to connect with public policy issues that relate to their personal experiences. Findings also indicated that the aapc is not an organized denomination, but rather a conglomeration of factions. Lack of an organized epicenter and lack of training and development of its leaders prevent this church from engaging in the public sphere. Although members embrace their responsibility to care for the needs of others, the church lacks a collective response to community issues. Findings may be used to prepare the next generation of aapc leaders to unify the church to offer spiritual solutions to public policy issues.